2023
DOI: 10.3390/foods12040820
|View full text |Cite
|
Sign up to set email alerts
|

Flavor Precursors and Volatile Compounds Improvement of Unfermented Cocoa Beans by Hydrolysis Using Bromelain

Abstract: Cocoa fermentation is an essential process that produces flavor precursors. However, many small farmers in Indonesia directly dry their cocoa beans without fermentation due to low yield and long fermentation time, resulting in fewer flavor precursors and cocoa flavor. Therefore, this study aimed to enhance the flavor precursors, particularly free amino acids and volatile compounds, of unfermented cocoa beans by hydrolysis, using bromelain. Unfermented cocoa beans were previously hydrolyzed with bromelain at co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…The results of this study are similar to those of Tamimi et al (2023), who reported that the DH of dry cocoa beans incubated for 8 h increased with rising Flavourzyme ® concentration. Meanwhile, different results were reported by Purbaningrum et al (2023); the DH of dry cocoa beans did not increase considerably after enzyme addition at concentrations ranging from 3.5 U/mL to 10.5 U/mL during 8 h of incubation. In this study, the enzyme concentration of 3.3 U/mL was selected and then used to determine incubation time.…”
Section: Effect Of Papain Concentration On the Degree Of Hydrolysismentioning
confidence: 63%
See 3 more Smart Citations
“…The results of this study are similar to those of Tamimi et al (2023), who reported that the DH of dry cocoa beans incubated for 8 h increased with rising Flavourzyme ® concentration. Meanwhile, different results were reported by Purbaningrum et al (2023); the DH of dry cocoa beans did not increase considerably after enzyme addition at concentrations ranging from 3.5 U/mL to 10.5 U/mL during 8 h of incubation. In this study, the enzyme concentration of 3.3 U/mL was selected and then used to determine incubation time.…”
Section: Effect Of Papain Concentration On the Degree Of Hydrolysismentioning
confidence: 63%
“…These findings corroborate with Tamimi et al (2023), who reported that Flavourzyme ® can only increase the levels of four types of FAAs including tyrosine, valine, phenylalanine, and leucine. Meanwhile, the hydrolysis of dried cocoa beans using bromelain increased the concentrations of almost all types of FAAs detected (Purbaningrum et al, 2023). During fermentation, hydrophobic FAA contents increased significantly (p < 0.05), particularly valine, leucine, isoleucine, and phenylalanine.…”
Section: Free Amino Acidsmentioning
confidence: 94%
See 2 more Smart Citations
“…Bromelain is an effective proteolytic enzyme obtained from the fruit or stem of a pineapple ( Ananas cosmosus ). Bromelain has a broad specificity for protein breakdown, particularly in hydrophobic amino acid residues, and cleaves proteins in the carbonyl end of lysine, alanine, tyrosine, and glycine 10 , 11 . The molecular weight of bromelain is 23 to 37.0 kDa.…”
Section: Introductionmentioning
confidence: 99%